A PREPARATION OF THE TEACHING PRACTICUM IN BATAM-INDONESIA - Hidayat Polim (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2022)
This study gathered data from Pre-Service Teachers (PSTs) in preparation for teaching practicum at a university in Indonesia. The study utilized a qualitative approach to comprehend the current practices in preparing participants of the teaching practicum and identifying the essential aspects needed to be addressed by research participants (PSTs, Practicum Supervisors, and Classroom Supervisors). The study found several courses that have helped PSTs in scaffolding their journey toward their practicum, including curriculum and material development, micro-teaching, and practicum orientation. However, as PSTs conduct their practicum, the dynamic and challenges were inevitably evident throughout the journey. The skills and knowledge they have studied have not been able to be fully utilized in the teaching practicum. These are reflected in their responses related to their confidence handling classroom management, language skills, identifying their role as practicum teacher, and the effectiveness of the current practice of classroom observation. The study concludes the importance of adjusting and reflecting on relevant aspects and knowledge that need to be integrated into the preparation of the teaching practicum. A systematic and continual innovation will need to be the focus of stakeholders in the teacher education prior to the teaching practicum.